Managerial Performance Strategy Through Partnership and Member Participation on the Performance of the Cooperative in Banjarmasin - Fanlia Prima Jaya (PT. Hanken SUkses Jaya, 2022)
Performance Cooperative who excel will be realized if the Partnership and Participation Members through the Performance Managerial implemented with either. The research aims to obtain clarity regarding Profile Partnership, Profile Participation Members, Profile Performance Managerial and Profile Performance Cooperative, and get clarity relationships Partnerships and Participation of members and their influence on performance managerial and Performance Cooperative. The method of research that is used is Explanatory Survey Method, Object Research this is the whole cooperative active that exist in the city of Banjarmasin, and drawn samples as a unit of analysis is the Cooperative Primary active and spread in Banjarmasin with as many as 75 respondents were represented by managers or administrators cooperatives are. Analysis using the Partial Least Square (PLS) model. Results The study showed Partnership is influential significantly toward Performance Managerial. Still, the Partnership does not impact Cooperatives' Performance. The participation of members of an effect on the Performance of Managerial and Performance Cooperative, Partnership and Participation Members are simultaneously influenced significantly to Cooperatives' Performance through Performance Managerial.